Pilot Testing an Asynchronous Online Harm Reduction and Pharmacotherapy Stigma Reduction Training for Substance Use Treatment Professionals - Sulzer, Sandra H. (Journal of drug issues, 2025)
Harm reduction and pharmacotherapy approaches to addressing substance use disorder are evidence-based practices for reducing adverse health outcomes. However, professional stigma toward these approaches impedes implementation. In this pilot study, professionals working in substance use treatment services received a 4-hour asynchronous online harm reduction and pharmacotherapy training. Pre- and post-training surveys used Likert-scale questions to assess attitudes and planned actions. Four of the 23 survey items demonstrated a significant change in pre- to post-attitudes and planned actions relating to harm reduction or pharmacotherapy. These items included less attitudinal stigma towards: methadone and buprenorphine (p = .021), overdose prevention sites/“drug consumption facilities” (p = .025), and naloxone distribution (p = .017), as well as lower intent to primarily promote abstinence-based interventions (p = .007). This study demonstrated that online asynchronous educational interventions show promise for reducing stigmatizing attitudes towards evidence-based practices among substance use treatment professionals.